2017
DOI: 10.1007/s11605-017-3370-9
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Optimal Quantitative Threshold for Preoperative Albumin Level Before Elective Colorectal Surgery

Abstract: This study objectively determines that a threshold preoperative serum albumin of ≥3.9 mg/dL is associated with improved outcomes in elective colorectal surgery patients. Each 0.5 mg/dL decrease in albumin was progressively associated with increased risk for complications. Identifying a minimum albumin threshold has implications in perioperative optimization of patients undergoing colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Based on a database including 16,145 colorectal surgical patients, it was found that patients with preoperative SA < 3.9gdL À1 were at higher risk of a major complication (OR 1.18, 95% CI 1.07-1.30, p ¼ 0.0007), any complication (OR 1.18, 95% CI 1.08-1.29, p ¼ 0.0002) and prolonged LOS. Interestingly, each decrease in SA by 0.5gdL -1 was associated with increased risk (Bendersky et al 2017). In our study, preoperative SA was found to be predictive of mortality and risk for reoperation (cut-off 4gdL À1 ) and of urinary tract infection (cut-off 3.8gdL À1 ).…”
Section: Discussionsupporting
confidence: 47%
“…Based on a database including 16,145 colorectal surgical patients, it was found that patients with preoperative SA < 3.9gdL À1 were at higher risk of a major complication (OR 1.18, 95% CI 1.07-1.30, p ¼ 0.0007), any complication (OR 1.18, 95% CI 1.08-1.29, p ¼ 0.0002) and prolonged LOS. Interestingly, each decrease in SA by 0.5gdL -1 was associated with increased risk (Bendersky et al 2017). In our study, preoperative SA was found to be predictive of mortality and risk for reoperation (cut-off 4gdL À1 ) and of urinary tract infection (cut-off 3.8gdL À1 ).…”
Section: Discussionsupporting
confidence: 47%
“…Our study findings have significant clinical implications, demonstrating the need to optimise nutrition in patients with IBD, who are often chronically malnourished during states of prolonged disease exacerbation. Although the prevalence of malnutrition in IBD by ICD coding from a representative in‐patient cohort of IBD patients is 5%‐10%, the probability of malnutrition just prior to IBD‐related surgery is likely much higher . Previous literature suggests that more than half of all patients may meet criteria for malnutriton at the time of IBD diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of malnutrition in IBD by ICD coding from a representative in-patient cohort of IBD patients is 5%-10%, 37 the probability of malnutrition just prior to IBD-related surgery is likely much higher. 38 Previous literature suggests that more than half of all patients may meet criteria for malnutriton at the time of IBD diagnosis. 39 Furthermore, it is likely that malnutrition especially in acute care settings may be under-reported and not diagnosed in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative serum albumin level is strongly associated with outcomes following various types of gastrointestinal surgery, including gastric, pancreatic, and colorectal surgery , as well as non‐gastrointestinal surgery . The association between serum albumin and IAI is controversial .…”
Section: Introductionmentioning
confidence: 99%